Editor's Introduction and Review: Coordination and Context in Cognitive Science. (8th November 2017) - Kello, Christopher T.
Abstract: The role of coordination in cognitive science has been on the rise in recent years, in terms of coordination among neurons, coordination among sensory and motor systems, and coordination among individuals. Research has shown that coordination patterns corresponding to cognitive activities depend on the various contexts in which the underlying interactions are situated. The present issue of Topics in Cognitive Science centers on studies of coordination that address the role of context in shaping or interpreting dynamical patterns of human behavior. This introductory article reviews some of the prior literature leading up to current and future research on coordination and context in cognitive science. Abstract : The literature on coordination within and between individuals is reviewed, with an emphasis on the inherent transience of coordination patterns in behavioral activity. This transience is integral to understanding cognitive activity as flexible patterns of coordination in brain, body, and environment. Kello reviews the articles in this special issue as contributions to understanding the role of context in shaping or interpreting coordination patterns in human behavior.